MALE AND FEMALE TEACHERS ROLES IN ASSESSMENT OF SPEAKING SKILL - Razali, Khairil; Isra, Muhammad (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2016)
This study aimed to explore about teachers’ assessment and the various activities in assessing students’ speaking skill as well as teachers’ reasons at senior high school. Through interview and qualitatively observation and analysis, the findings indicate that male and female teacher involved in speaking activities in the classroom toward assessing students’ speaking skill through different ways. They were discussion, reporting, picture describing, and role play. Practicality, usefulness, wash back and authenticity are another reasons behind the application of those speaking activities. In short, the various speaking assessment tasks would be useful in assessing students’ speaking skill.